(untitled) (British Journal of Global Ecology and Sustainable Development, 2025)
This article addresses the issue of salinity patches variability in irrigated areas, which is considered one of the most critical meliorative challenges. Traditional field surveys for detecting and monitoring soil salinization are time-consuming and costly; therefore, the study focuses on the application of modern remote sensing technologies. The research improves methodologies for identifying and analyzing saline spots based on satellite imagery and drone data. In particular, spectral indices such as NDVI, SI, and other vegetation–soil indicators were employed to assess the spatial and temporal dynamics of soil salinity. The results provide insights into the distribution and intensity of salinity processes, enabling better understanding of their variability across time and space. The findings are of practical importance for planning effective reclamation measures, optimizing water resource management, and ensuring sustainable agricultural production. Moreover, the proposed approach offers farmers and land management organizations a rapid and accurate tool for monitoring salinity processes in irrigated lands.